Magnetic targeting of paclitaxel-loaded poly(lactic-co-glycolic acid)-based nanoparticles for the treatment of glioblastoma - Ganipineni LP (Dove Medical Press, 2018)
Lakshmi Pallavi Ganipineni,1 Bernard Ucakar,1 Nicolas Joudiou,2 John Bianco,1 Pierre Danhier,2 Mengnan Zhao,1 Chiara Bastiancich,1 Bernard Gallez,2 Fabienne Danhier,1,* Véronique Préat1,* 1Université catholique de Louvain, Advanced Drug Delivery and Biomaterials Research Group, Louvain Drug Research Institute, Brussels, Belgium; 2Université catholique de Louvain, Louvain Drug Research Institute, NEST Nuclear and Electron Spin Technologies Platform, Brussels, Belgium *These authors contributed equally to this work Introduction: Glioblastoma (GBM) therapy is highly challenging, as the tumors are very aggressive due to infiltration into the surrounding normal brain tissue. Even a combination of the available therapeutic regimens may not debulk the tumor completely. GBM tumors are also known for recurrence, resulting in survival rates averaging <18 months. In addition, systemic chemotherapy for GBM has been challenged for its minimal desired therapeutic effects and unwanted side effects. Purpose: We hypothesized that paclitaxel (PTX) and superparamagnetic iron oxide (SPIO)-loaded PEGylated poly(lactic-co-glycolic acid) (PLGA)-based nanoparticles (NPs; PTX/SPIO-NPs) can serve as an effective nanocarrier system for magnetic targeting purposes, and we aimed to demonstrate the therapeutic efficacy of this system in an orthotopic murine GBM model. Materials and methods: PTX/SPIO-NPs were prepared by emulsion–diffusion–evaporation method and characterized for physicochemical properties. In vitro cellular uptake of PTX/SPIO-NPs was evaluated by fluorescence microscopy and Prussian blue staining. Orthotopic U87MG tumor model was used to evaluate blood–brain barrier disruption using T1 contrast agent, ex vivo biodistribution, in vivo toxicity and in vivo antitumor efficacy of PTX/SPIO-NPs. Results: PTX/SPIO-NPs were in the size of 250 nm with negative zeta potential. Qualitative cellular uptake studies showed that the internalization of NPs was concentration dependent. Through magnetic resonance imaging, we observed that the blood–brain barrier was disrupted in the GBM area. An ex vivo biodistribution study showed enhanced accumulation of NPs in the brain of GBM-bearing mice with magnetic targeting. Short-term in vivo safety evaluation showed that the NPs did not induce any systemic toxicity compared with Taxol® (PTX). When tested for in vivo efficacy, the magnetic targeting treatment significantly prolonged the median survival time compared with the passive targeting and control treatments. Conclusion: Overall, PTX/SPIO-NPs with magnetic targeting could be considered as an effective anticancer targeting strategy for GBM chemotherapy. Keywords: nanomedicine, glioblastoma, magnetic targeting, nanoparticles, PLGA-based nanoparticles